FOOT DEFORMATIONS IN COCONUT TREE CLIMBERS OF SOUTH INDIA - George, Bincy M.; Kumar, Arunachalam; Rao, Muddanna S. (Journal of Health and Allied Sciences NU, 2013)
There are observable foot changes in professional coconut tree climbers of south India, but those are not reported in literature. Objective of the present study was to quantify the foot adaptations in south Indian coconut tree climbers.Data from a total of 220 male volunteers, between 18-55 years of age, engaged in the profession of coconut tree climbing were collected to find the anatomical changes in foot in them.The data revealed the coconut tree climbers are having prominent pes cavus, varus foot and abducted great toe. The adaptation pattern of foot varies depending upon the pressure it is subjected to bear.This study establishes an occupationally induced form of foot deformations or adaptations which are not, reported much in the literature.
Keywords: Coconut tree climbers; Occupational adaptations; Foot